The effect on economic development of creative class versus human capital: panel evidence from German regions. Issue 1 (2nd January 2021) - Tiruneh, Esubalew Alehegn; Sacchetti, Silvia; Tortia, Ermanno C.
ABSTRACT: The creative class thesis considers the creative class, compared to human capital, as a better driver of regional economic development. We test this thesis for Germany. We measure creative class and human capital by occupation and education, respectively using classification codes from The Sample of Integrated Labor Market Biographies (SIAB), and proxy regional economic development by per capita income and employment. Our panel estimation results with system GMM show that the human capital effect on per capita income is substantially stronger than the creative class, while the creative class drives employment far better than human capital does. The evidence does not support the notion that the creative class drives development better than human capital.